Modification of local diets to improve vitamin A, iron and protein contents for children aged 6 to 23 months in Kagera,Tanzania - Mbela, D.E.N.; Kinabo, J.; Mwanri, A.W.; Ekesa, B. (African Journal of Food, Agriculture, Nutrition and Development, 2018)
The banana-based farming system of Kagera region of Tanzania has good edible food diversity. However, households still consume monotonous diets, which are mainly energy dense and have inadequate content of micronutrients. To enrich the preferred energy-rich diets, this study formulated dishes with improved content of vitamin A, iron and protein for children aged between 6 to 23 months. Mothers (n = 50) were randomly selected from Izimbya ward and participated in a recipe development exercise whereby five recipes modified from the traditional banana based ‘katogo’/’matoke’ and three types of porridges were developed using locally available foods such as bananas, beans, amaranths, red palm oil, pumpkin, groundnut, maize and orange-fleshed sweet potato (OFSP). Mothers were asked to give options of improving the porridge intended to be fed to children as well as to propose means of improving the local banana diets. Vitamin A was increased by red palm oil, OFSP, pumpkin fruit and leaves in the modified recipes. Furthermore, red kidney bean and groundnut contributed a significant amount of protein and iron in the recipes. Red kidney beans formed a good source of iron, protein and energy when incorporated in complementary foods. The family dishes and children’s local popular dishes were modified to improve the consistency by making a purée to increase food intake and, therefore, vitamin A, iron and protein. The developed recipes contained more than 100% recommended daily allowance (RDA) for vitamin A and protein. The conversion factor of 12:1 for beta-carotene was used. The RDA for iron ranged from 61% to 99%. Vitamin A, iron, protein and energy content of modified recipes ranged from 108-2768 RAE, 6-17 mg, 28-56 g and 697-1635 kcal, in 500g consumption portion, respectively. These levels meet the RDAs for breastfed and nonbreastfed children. The created recipes based on locally available and affordable ingredients have a potential to meet RDAs of vitamin A, iron and protein for children aged 6 to 23 months in the banana-based system and other communities in Africa with the same settings. The communities need to establish home gardens so as to use vegetables and foods which are cheap and good sources of micronutrients and protein.